PEMBERDAYAAN MASYARAKAT DALAM MENINGKATKAN USAHA MELALUI PROGRAM PELATIHAN TATA RIAS KECANTIKAN - Omo Permana (Media Nusantara, 2022)
This research supported by Ujungberung since many of citizens who dropped out of school and the more unemployment, this condition that the community, less creative independent, and dynamic, based on this reality, needed a place to distribute and developing the potential, skills so as to improve the lives of the community. especially for the study. The goal is to know:) planning community empowerment in improving undertaking through training program. beauty make-up the management of 2) training program. beauty make-up whatever the 3) supporters and that in the training program. beauty make-up 4) evaluation beauty make-up training program held in PKBM Ujungberung. of copyright. Study theory that used in this research was: A. The concept of community empowerment. B. The development of an increase in the income of the. C. Program concept training. D. The concept of hairdos beauty. E. The concept of education non-formal. The methodology using descriptive with a qualitative approach. A middleman: the data the observation, interview, and documentation. The subject is: Institution manager, a tutor and the study. Discussion and the outlines of: 1) planning empowerment that included the community in fact carried out by the community will receive benefits felt by the community. The implementation of the 2) learning as learning a participative, because there are adults interact, and the participation of all parties are active and affect each other very dominated.3) supporting factors and that all can be overcome with a settlement and to make decision to reach consensus. 4) evaluation training is part of any process or training from the planning stage, Implementation and follow up of a training. In conclusion empowerment activities with the training hairdos beauty by PKBM BCU run smoothly and produces an output that in accordance with the planned.Keywords: Empowerment, The Community, Training, Makeup Beauty